Ambiguities in a partial-wave analysis of γp→ π0p with truncation in total angular momentum; Journal of Physics G: Nuclear and Particle Physics; Vol. 50, iss. 5 - Fiks (Fix) A. I. Alexander Ivanovich (2023, 2023)
Title screen